The ion channel TRPV5 regulates B-cell signaling and activation - Mahtani, Trisha; Sheth, Hena; Smith, L. K.; Benedict, Leshawn; Brecier, Aurelie; Ghasemlou, Nader; Treanor, Bebhinn (Frontiers in Immunology, 2024)
B cell activation triggers the release of endoplasmic reticulum calcium stores by the store operated calcium entry (SOCE) pathway resulting in calcium influx by calcium release activated calcium (CRAC) channels on the plasma membrane. B cell specific murine knockouts of SOCE do not impact humoral immunity, suggesting that alternative channels may be important. We identified a member of the calcium permeable transient receptor potential (TRP) ion channel family, TRPV5, as a candidate channel expressed in B cells by a qPCR screen. We found TRPV5 polarized to B cell receptor (BCR) clusters upon stimulation in a PI3K-RhoA dependent manner.To further investigate the role of TRPV5 in B cell responses, we generated a murine TRPV5 knockout (KO) by CRISPR-Cas9. TRPV5 KO mice have normal B cell development and mature B cell numbers. Surprisingly, calcium influx upon BCR stimulation in primary TRPV5 KO B cells was not impaired; however, differential expression of other calcium-regulating proteins, such as ORAI1, may contribute to a compensatory mechanism for calcium signalling in these cells. We demonstrate that TRPV5 KO B cells have impaired spreading and contraction in response to membrane-bound antigen. Consistent with this, TRPV5 KO B cells have reduced BCR signalling measured by phospho-tyrosine residues. Thus, our findings identify a role for TRPV5 in BCR signalling and B cell activation.